Efficiency and Safety of Scleral Lenses in Rehabilitation of Refractive Errors and High Order Aberrations After Penetrating Keratoplasty. Issue 5 (May 2021) - Penbe, Aysegul; Kanar, Hatice Selen; Simsek, Saban
Abstract : Objectives: Visual rehabilitation after penetrating keratoplasty (PK) has difficulties linked to the high spherical and/or cylindric refractive errors with high order aberrations (HOAs) based on the ocular surface irregularities. We aimed to present the scleral contact lens (SCL)-induced complications and improvements in refractive errors and HOA with SCL fitting in post-PK patients. Methods: In this prospective study, 38 eyes of 35 patients who underwent PK and using SCLs were included. Uncorrected visual acuity, best-corrected visual acuity (BCVA), spherical equivalence, manifest astigmatism (Cyl), keratometry, and wavefront analyses of HOAs with corneal topography of all patients were measured before SCL and after 8 hrs of SCL wearing-on. The endothelial cellular density (ECD) changes at 6 months were also recorded. Any complications related to SCL were noted. Results: All patients showed an improvement in visual acuity with SCL. Uncorrected visual acuity before SCL fitting was 1.15±0.26 log of minimal angle of resolution (logMAR) and BCVA was 0.84±0.24 logMAR. The contact lens-corrected visual acuity decreased to 0.13±0.09 logMAR. Spherical equivalence, Cyl, and keratometry parameters decreased significantly with SCL. The anterior corneal HOAs, coma, and astigmatism coefficients decreased significantly. Conjunctival prolapse (in one eye) and graft rejection episode (in two eyes) were observed during follow-up time (14.25±1.3 months) and they restarted to use SCLs after treatment. The ECD decrease was similar with those who not using SCLs after PK in the literature. Conclusion: Our results indicate that scleral lenses may be a safe and effective option for the treatment of corneal astigmatism and HOAs associated with PK.